2014
DOI: 10.1111/beer.12076
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance of socially responsible investing (SRI): what have we learned? A meta‐analysis

Abstract: International audienceWith a meta-analysis of 85 studies and 190 experiments, the authors test the relationship between socially responsible investing (SRI) and financial performance to determine whether including corporate social responsibility and ethical concerns in portfolio management is more profitable than conventional investment policies. The study also analyses the influence of researcher methodologies with respect to several dimensions of SRI (markets, financial performance measures, investment horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
310
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(334 citation statements)
references
References 161 publications
18
310
5
1
Order By: Relevance
“…However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19]. Those studies also found no significant CSR-performance linkage [22,23]. The results mean that synergy of CSR could also be generated in M&A activities.…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19]. Those studies also found no significant CSR-performance linkage [22,23]. The results mean that synergy of CSR could also be generated in M&A activities.…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 99%
“…The results of empirical studies regarding the economic impacts of CSR are also mixed. Some studies have found no significant relationship between CSR and a firm's economic performance [22,23]. Other studies provide evidence of a significant relationship between CSR and corporate performance [24][25][26][27].…”
Section: Corporate Social Responsibility and Firm Performancementioning
confidence: 99%
“…Thus, ethical investments, socially responsible investing, microcredit, and social banking have rapidly developed because financial institutions and intermediaries have enhanced their financial decision-making process by incorporating ethical choices and social objectives (Editorial "Research in International Business and Finance," 2017). The initial studies concerning this issue have questioned whether the ESG integration in financial decisions and socially responsible investment performance still rewards investors and companies through the tangible financial performance achieved by companies (Friede et al, 2015;Orlitzky, Schmidt, & Rynes, 2003) and investors (Revelli, 2017;Revelli & Viviani, 2015).…”
Section: The Impact Of Esg On Financial Decision-makingmentioning
confidence: 99%
“…These authors pointed out that the results are highly dependent on the study methods applied in each paper. Revelli and Viviani [37], also performing a meta-analysis on these topics, confirmed that no relevant differences are found between the performances between SRI and conventional funds. The final sentence of this paper deals with a central challenge for the research in this field: "Beyond the debate on the financial performance of SRI, we need to understand how SRI modifies the behaviours of companies and investors, as well as whether this way of investing is efficient in achieving the objective of greater ethicality and social responsibility".…”
Section: Corporate Social Responsibility and Socially Responsible Invmentioning
confidence: 67%